2018
DOI: 10.1590/1806-9282.64.09.814
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of Brazilian oncological patients seen by a reference oncology center of the public health system and who migrate in search of adequate health care

Abstract: SUMMARY INTRODUCTION Structural disparities between different Brazilian regions in public health system cause patients to migrate in search of better conditions to treat their diseases. Besides patient’s discomfort, there is a concentration of care in large centres, causing overload to current capacity. OBJECTIVE To evaluate migratory flow and associated factors in a reference service in oncology. METHODS Cross-sectional study conducted at a referral oncology service in Great ABC region of São Paulo. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
9
0
1
Order By: Relevance
“…A large portion of the Brazilian population undergoing cancer treatment in public hospitals in the country has a low level of education and income. 30,31 The results of the study showed that the largest proportion of participants had a low level of education. It was not possible to identify an association between educational level with aggressiveness in the EOL care and PC consultation, as shown in our previous study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A large portion of the Brazilian population undergoing cancer treatment in public hospitals in the country has a low level of education and income. 30,31 The results of the study showed that the largest proportion of participants had a low level of education. It was not possible to identify an association between educational level with aggressiveness in the EOL care and PC consultation, as shown in our previous study.…”
Section: Discussionmentioning
confidence: 94%
“…Through the universal Brazilian Unified Health System, everyone has the right to free access to health services. Health resources come from public budgets and, therefore, generate social and economic implications for the treatment offered to cancer patients, 30 such as limited therapeutic options. In this scenario, physicians may feel encouraged to finish the standard oncology treatment, curative, and initiate a discussion and transition to PC.…”
Section: Discussionmentioning
confidence: 99%
“…These results are possibly associated with women in these regions having higher difficulty accessing the oncological treatment centres compared to the South and Southeast regions, where the highest number of mortality is observed in women aged greater than 60 years [21]. The structural differences between the different regions in Brazil in the public health system lead women to migrate to search for better conditions in treating their diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, cancer is the second major cause of death among those aged ≥ 70 years [ 1 ]. There are socioeconomic differences between Brazilian regions and cities, and these discrepancies influence the availability of diagnostic methods and treatments, determine migratory phenomena, and could possibly be related to differences in oncological outcomes [ 2 ].…”
Section: Introductionmentioning
confidence: 99%